Trend analysis of batch to batch consistency during quality assessment of biological medicinal products - D. S. Davydov (Биопрепараты: Профилактика, диагностика, лечение, 2018)
The statistical analysis of trends in the quantitative data obtained during laboratory evaluation is one of the most important conditions of ensuring quality. Equally, the analysis of trends is necessary to confirm the compliance of biological medicinal products to the requirements of manufacturers’ quality standards and to ensure the reliability of laboratory tests. The article briefly surveys the positions of the World Health Organization (WHO) and the International Organization for Standardization (ISO) on the analysis of trends in the production of biological medicinal products, especially vaccines, as well as on methodological approaches to the planning and organization of random sampling checks.